Mental healthcare for psychiatric inpatients during the COVID-19 epidemic - Yong Zhang (General Psychiatry, 2020)
During this 2019 coronavirus disease (COVID-19) pneumonia epidemic, some experts have expressed concern for the mental healthcare of different types of population groups. However, hospitalised patients with severe mental illness are seemingly overlooked. Psychiatric patients are still a vulnerable group who need to obtain more attention and respect, particularly during the COVID-19 outbreak in China. In this commentary, we briefly introduce the situation of hospitalized patients with severe mental illness and suggest some effective measures that should be rapidly undertaken to reverse current challenges.